God and the World: Panentheism in Modern Orthodox Christianity - Ladouceur, Paul (Zygon, 2025)
Panentheism is an unsettling and controversial notion in modern Orthodox Christianity. Some Orthodox theologians explicitly identify themselves as panentheists, while others reject panentheism as incompatible with Orthodox tradition. Sergius Bulgakov presents his theology of Divine Wisdom (sophiology) as panentheist, distinguishing it from pantheism. Orthodox theologians such as Kallistos Ware and Andrew Louth associate with panentheism. Whereas Orthodox critics (notably, Georges Florovsky and Nicolas Lossky) see panentheism as a subspecies of pantheism (hence, unacceptable), Bulgakov and other modern Orthodox theologians regard it as a subspecies of theism (hence, acceptable). The issue revolves around divergent theologies of creation and how God relates to creation. Earlier, the issue was entwined in the controversy over Bulgakov’s theology of Divine Wisdom. By the twenty-first century, the focus is on looking for compatibilities in patristic theology, especially the logoi of creation in Maximus the Confessor and the divine energies in Gregory Palamas. The transition in Orthodox thought from a mostly aggressive stance towards panentheism to an irenic one is promising, but Orthodox theologians have yet to engage meaningfully in the ongoing dialogues on panentheism.